A novel MnO2/MXene composite prepared by electrostatic self-assembly and its use as an electrode for enhanced supercapacitive performance. Issue 1 (30th November 2018) - Chen, Shu; Xiang, Yuanfang; Xu, Weijian; Peng, Chang
Abstract : A novel MnO2 /MXene composite prepared by electrostatic self-assembly and its use as an electrode for enhanced supercapacitive performance. Abstract : MXene is a new 2D transition metal carbide possessing metallic conductivity and hydrophilic surfaces. It has drawn widespread attention as a potential material for electrode use. However, the applications of MXene are limited by its property of low electrical capacity. In this paper, a novel MnO2 /MXene composite is prepared by electrostatic self-assembly. Firstly, delaminated MnO2 nanosheets are obtained through the intercalation delamination of multilayered H-MnO2 in a cationic Gemini surfactant (Gem) solution, leading to a positively charged surface. Then, the positive MnO2 nanosheets are assembled on negative MXene nanosheets through electrostatic self-assembly to form a MnO2 /MXene composite. The characterization results show that the MnO2 nanosheets are intimately assembled on the MXene nanosheets. As an electrode material, the MnO2 /MXene composite displays a specific capacitance of 340 F g −1 at 1 A g −1, which is three times the performance of an MXene electrode. In addition, the MnO2 /MXene electrode shows a high retention rate (90.3% retention at 10 A g −1 ) and good cycling life (87.6% of the initial specific capacitance is retained after 2000 cycles at 4 A g −1 ). The properties of the proposed composite are attributed to the excellent conductivity of MXene and the high specific capacitance of MnO2 .